2021
DOI: 10.3390/agronomy11122500
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Leaf Extract Enhanced Growth, Yield, and Silybin Content While Mitigating Salt-Induced Adverse Effects on the Growth of Silybum marianum

Abstract: Silybin A and B are two major hepatoprotective flavonolignans produced predominantly in Silybum marianum fruits. Similar to other plant secondary metabolites, silybin production is enhanced by biotic or abiotic stresses under the expanse of plant growth and yield. In this study, a novel strategy for enhancing silybin production was investigated by applying a natural plant growth enhancer, moringa leaf extract (MLE), to the S. marianum plants cultivated under salinity abiotic stress. The experiment was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…[20]. Three CHS genes, namely CHS 1, CHS 2, and CHS 3, have been identified and their expressions were associated with the accumulation of silymarin in S. marianum [21,22]. Salicylic acid, as a plant elicitor, has been shown in multiple studies to elevate the activity of the CHS enzyme, which is involved in flavonoid production [13,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…[20]. Three CHS genes, namely CHS 1, CHS 2, and CHS 3, have been identified and their expressions were associated with the accumulation of silymarin in S. marianum [21,22]. Salicylic acid, as a plant elicitor, has been shown in multiple studies to elevate the activity of the CHS enzyme, which is involved in flavonoid production [13,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress enhances the production of ROS that impairs protein and DNA, carbohydrates metabolism, chlorophylls, mitochondria and lipid. Salinity stress exhibits detrimental effects on root activities, which diminishes water and nutrient uptake and accumulation, which may change many physiological traits (Yap et al, 2021;Yue et al, 2022). Previous studies reported that salinity increases the accumulation of toxic ions and ROS production and reduces leaf water potential and relative water contents (Arif et al, 2020;Sarwar et al, 2021).…”
Section: Antioxidant Enzymes and Ros Scavengingmentioning
confidence: 99%
“…Plant leaf samples were taken 270 days from 10 harvested plants and dried for 48 h at 60 • C. Quantification of nitrogen (N), phosphorus (P), and potassium (K) was performed as previously described [25].…”
Section: Mineral Compositionmentioning
confidence: 99%
“…Four S. marianum plants that were 270 days old had the pigments (chlorophyll a (Chl-a), chlorophyll b (Chl-b), and carotenoid) extracted with 80% acetone from the third bottom fresh leaf [25].…”
Section: Photosynthetic Pigment Determinationmentioning
confidence: 99%
See 1 more Smart Citation